2017
DOI: 10.1007/s11255-017-1730-8
|View full text |Cite
|
Sign up to set email alerts
|

B-lines score on lung ultrasound as a direct measure of respiratory dysfunction in ICU patients with acute kidney injury

Abstract: LUS can be used for functional lung evaluation and identification of patients with increase pulmonary water content and decrease PaO/FiO ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…Our results suggest that the BLS is highly correlated with the PaO 2 /FiO 2 ratio, which is consistent with previous data revealing that the LUS score was significantly correlated with the oxygenation index in critical care patients . These findings are also consistent with those reported by Bilotta et al and Ciumanghel et al indicating that the BLS was strongly correlated with the PaO 2 /FiO 2 ratio in neurocritical care patients ( r = −.8) and in patients with acute kidney injury. Cagini et al found that LUS could detect EVLW increases after major pulmonary resection and a significant inverse correlation was also observed between the B‐line score and the PaO 2 /FiO 2 respiratory ratios.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that the BLS is highly correlated with the PaO 2 /FiO 2 ratio, which is consistent with previous data revealing that the LUS score was significantly correlated with the oxygenation index in critical care patients . These findings are also consistent with those reported by Bilotta et al and Ciumanghel et al indicating that the BLS was strongly correlated with the PaO 2 /FiO 2 ratio in neurocritical care patients ( r = −.8) and in patients with acute kidney injury. Cagini et al found that LUS could detect EVLW increases after major pulmonary resection and a significant inverse correlation was also observed between the B‐line score and the PaO 2 /FiO 2 respiratory ratios.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with AKI, the B-line score was correlated negatively with the partial pressure of oxygen in relation to the inspired oxygen concentration (PaO 2 /FiO 2 ratio). 130 Improving the evaluation of organ congestion using POCUS may lead to a pre-emptive initiation of RRT in patients with severe AKI before an acute complication develops, such as acute pulmonary edema requiring emergency endotracheal intubation. Furthermore, repeated assessment of these markers may be useful to guide fluid removal with diuretics or with ultrafiltration after the initiation of RRT.…”
Section: Early Diagnosis and Evaluating The Risk Of Progressionmentioning
confidence: 99%
“…Имеющиеся в литературе данные о наличии взаимосвязи между послеоперационной оксигенацией и ультразвуковой оценкой интерстициального синдрома и консолидации весьма противоречивы [6,20]. Так, у пациентов после обширных абдоминальных вмешательств подобной взаимосвязи установлено не было [6].…”
Section: Discussionunclassified
“…В этой же работе была показана удовлетворительная предиктивная способность ультразвуковой оценки степени консолидации легочной ткани в отношении отсроченной гипоксемии. Вместе с тем у пациентов с отеком легких на фоне развития острого повреждения почек взаимосвязь между количеством B-линий и гипоксемией прослеживалась весьма отчетливо [20]. Возможность ультразвука оценивать количество В-линий использовалась рядом авторов как маркер начинающейся гипергидратации и рекомендована для протоколов целенаправленной инфузионной терапии [21].…”
Section: Discussionunclassified
See 1 more Smart Citation